PRODUKSI DAN PENJUALAN ACTION FIGURE KARAKTER YANG DILAKUKAN TANPA SEIZIN PENCIPTA - Aulia Afifah (2022)
Law Number 28 of 2014 concerning Copyright defines Copyright as an exclusive right that arises automatically after the creation is in real or visualized form. The existence of a copyright aspect in an action figure character can not make it free from this. The production and sale of action figures needs to be carried out in accordance with the provisions of the applicable laws and regulations so that their actions do not violate and cause harm to the creator or copyright holders.The purpose of this research are to find out how is the implementation of copyright infringement on the production and sale of character action figures which is carried out without permission from creator of the fictional character, also the legal protection obtained for creators and copyright holders of fictional characters for these actions. This research uses normative juridical research methods and uses statue approach. The result of this research are that the production and sale of action figures carried out without permission has the potential to violate the economic rights of the creators of fictional characters, because adaptation of a work can only be done by the creator or the copyright holders. For creators or copyright holders who feel aggrieved the legal protection is regulated in the Copyright Law which includes criminal law instruments as well as civil law instrument.